Integrated transport from policy to practice - Givoni, Moshe; Banister, David (Routledge, 2010)
Addressing how the integration of transportation systems could promote more sustainable travel, this book covers case studies, governmental policy and future travel usage in this comprehensive look at how multimodal travel could become more cohesive.